Faktor Risiko Pneumonia Paska Operasi Bedah Pintas Arteri Koroner - Fadhilah, Vita Karima; Achmad, Chaerul; Afrianti, Rien; Santoso, Prayudi (The Indonesian Heart Association, 2024)
Background: Postoperative pneumonia (POP) is a common infectious complication of coronary artery bypass grafting (CABG), leading to significant morbidity, mortality, and increased healthcare costs. This study found that the prevalence of POP was nearly double that reported in previous studies, underscoring the urgent need to identify specific risk factors. These findings emphasize the importance of local data in refining preventive strategies and improving clinical outcomes in CABG patients. Material and Methods: This is a retrospective cohort study. The subjects comprised patients who underwent CABG procedures at a single institution between June 2020 and June 2024. A logistic regression analysis model for evaluating the risk of POP was established. Results: This study observed a POP rate of 41.7%, significantly exceeding the 2–24% range reported in previous studies. Key risk factors included elevated creatinine levels, eGFR <60 ml/min/1.73 m², and low early postoperative albumin. POP strongly correlated with prolonged hospitalization, with an odds ratio of 13.043 (95% CI: 6.130–27.751, p < 0.0001), underscoring its substantial impact on patient outcomes. Conclusions: The present study delineates renal impairment and hypoalbuminemia postoperative as pivotal risk factors for POP following CABG. It emphasizes the importance of tailored interventions, structured institutional practices, and continuous research to enhance preventive strategies and patient outcomes.